Borderline exegesis - Vaage, Leif E. (University Park, Pennsylvania : The Pennsylvania State University Press, 2014)
"A textual interpretation of the book of Job, the Gospel of Matthew, the Epistle of James, and Revelation. Includes analysis of the utopian imagination at work in a borderline exegesis"--Provided by publisher.
Introduction : another Bible that is borderline -- Into the whirlwind : God's answer to Job's complaint -- The economy, stupid! the teaching of Jesus in the Gospel of Matthew -- Interlude : displaced exegete: a scriptural biography -- Such a little thing! the tongue and alternate subjectivity in the Epistle of James -- Interrupting hope : the book of Revelation -- Conclusion : after the Bible : life's largesse.
Includes bibliographical references and index.
Print version record.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Bible; Electronic books; Criticism, interpretation, etc